1998
DOI: 10.1063/1.122508
|View full text |Cite
|
Sign up to set email alerts
|

Change in luminescence properties of porous Si by F2 and D2O exposure: In situ photoluminescence, Raman, and Fourier-transform infrared spectral study

Abstract: In situ photoluminescence (PL), Raman, and infrared (IR) spectra of porous Si (PS) during F2/D2O exposures were investigated. F2 exposure at 298 K resulted in a peak shift of PL band from 750 to 670 nm with an intensity reduction. IR spectra revealed that the surface hydrogenated Si of the PS was displaced by fluorinated one. By subsequent D2O exposure, the PL band further shifted to a shorter wavelength with a significant intensity increase: IR bands due to surface oxides as well as SiD and SiOD bonds were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…The IR spectrum of the as-anodized PS (a) is well characterized by the strong bands due to silicon hydrides (Si-H x ; x = 1,2,3) and also by the very weak bands due to silicon oxide. 7,8) It is found that the RTO (b) and RTOQN (c) treatments lead to a severe oxidation of the silicon particles and consequently the bands due to silicon oxide are observed strongly in place of the silicon hydride bands. As can be seen clearly from Figs.…”
Section: Raman Ir Xps and Sem Observations Of Slow-and Fast-decay Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR spectrum of the as-anodized PS (a) is well characterized by the strong bands due to silicon hydrides (Si-H x ; x = 1,2,3) and also by the very weak bands due to silicon oxide. 7,8) It is found that the RTO (b) and RTOQN (c) treatments lead to a severe oxidation of the silicon particles and consequently the bands due to silicon oxide are observed strongly in place of the silicon hydride bands. As can be seen clearly from Figs.…”
Section: Raman Ir Xps and Sem Observations Of Slow-and Fast-decay Pmentioning
confidence: 99%
“…In contrast, porous silicon (PS) which is usually prepared from bulk silicon through anodization in hydrofluoric acid solutions has widely been investigated from both basic and applied viewpoints since the discovery of a visible photoluminescence (PL) from PS at room temperature. 1) It is well known that the PL of PS is sensitive not only to anodization conditions but also to post-treatments, including oxidation in air, 2) anodic oxidation 3,4) and boiling in tap water, 5) F 2 /H 2 O and thermoelectron/H 2 O treatments in vacuum conditions [6][7][8] etc. Furthermore, the rapid thermal oxidation (RTO) treatment of as-anodized PS brings about a significant blue shit of the original PL peak position from 650-800 nm (red) to 430-550 nm (blue-yellow).…”
Section: Introductionmentioning
confidence: 99%
“…Были приложены значительные усилия для реализации люминесцентных свойств PS в оптических структурах, однако низкая эффективность [12] и неста-бильность [1] оптических характеристик являются глав-ными проблемами. Нестабильность PS, как известно, возникает из-за трансформации наноструктуры PS при различных условиях формирования [2,3,13,14] и атмо-сферных условий [15,16]. Старение слоев PS индуцирует нестабильность сигнала PL, поскольку под воздействи-ем атомов кислорода происходит разрушение кремний-водородных (Si−H) связей в нанокристаллах (NC) крем-ния, а кислород может оставаться на поверхности или диффундировать вглубь кремниевых NC.…”
Section: Introductionunclassified
“…The experimental set-up used for in-situ PL, Raman, and IR measurements has been described elsewhere. 20,21) The PL as well as the Raman scattered light from the sample located in the UHV cell was dispersed by a polychrometer (JASCO CT25TP) and detected with a liquid-N 2 -cooled CCD detector (Princeton ST130). The detection system was interfaced to a personal computer (NEC PC-9801) for data acquisition and storage.…”
Section: Methodsmentioning
confidence: 99%
“…The absorption features appeared around 2100, 1100 and 900 cm À1 can be ascribed to the Si-H x stretches, Si-O stretch, and Si-H x deformation, respectively. [18][19][20]23) Fig . 3 Raman spectra of the PS of before (thermoelectron-treated sample:…”
Section: Thermoelectron and H 2 O Exposurementioning
confidence: 99%